Design of hose roller for firefighter: a fatigue study - Hakim Mustapha, Mohammad Luqman; Mahmood, Salwa; El Bakri, Helmy Mustafa; Abdul Rahman, Ismail; Azis, Noorul Azreen; Buang, Mohd Rizal (2023)
In a working environment, worker’s safety and health are the most critical considerations. Previous study discovered that firefighters are exposed to a great deal of ergonomic risk factors (ERF). ERF exposure during hose rolling includes awkward posture and forceful exertion. Therefore, the primary goal of this research paper is to fabricate an ergonomic hose roller for firefighters and conduct a fatigue analysis to determine the efficiency of the tool designed to safeguard firefighters against the risk of low back disorder (LBD). Hose roller testing is necessary to guarantee that it can withstand the weight of fire hoses while still being comfortable for users’ bodies. Fatigue analysis was conducted using Industrial Lumbar Motion Monitor (i-LMM) equipment to evaluate LBD risk during hose rolling. Manual handling contributes 57.67% to the total average percentage value used to compute LBD risk results, while utilizing a roller tool, the hose rolling procedure yields a 27% LBD risk limit value. The design of experiment (DOE) method should be used in future studies to gather more information for the LBD risk assessment